Digital Marketing Communication Strategy for Wedding Organizers in Hastana DPW North Sumatra in Improving the Image and Sales of Wedding Organizers - Herawati, Ivo; Ginting, Rahmanita; Faustyna, Faustyna (Mahesa Research Center, 2025)
This article or writing aims to find out how the digital marketing communication strategy in Hastana DPW SUMUT improves the image and sales of Wedding Organizers and to find out the inhibiting factors. This study uses a descriptive qualitative method to understand the communication strategy of HASTANA DPW SUMUT in improving the image of wedding organizers through Instagram. Data were obtained through interviews with the Head of HASTANA DPW SUMUT, social media observations, and documentation. Data analysis was carried out inductively, following the Miles and Huberman model, with triangulation to ensure validity. The results of this study indicate that the digital marketing strategy by the wedding organizer HASTANA DPW North Sumatra has succeeded in building a positive image, increasing sales, and expanding customer reach. Through social media and participation in wedding exhibitions, WO strengthens public trust and maintains customer loyalty. Focusing on transparency, quality, and understanding customs helps WO face challenges and strengthen its position in the wedding industry.